2022
DOI: 10.3390/cryst12020172
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet-Visible-Near Infrared Broadband Photodetector Based on Electronspun Disorder ZnO Nanowires/Ge Quantum Dots Hybrid Structure

Abstract: Ultraviolet-visible-near infrared broadband photodetectors have significant prospects in many fields such as image sensing, communication, chemical sensing, and day and nighttime surveillance. Hybrid one-dimensional (1D) and zero-dimensional (0D) materials are attractive for broadband-responsive photodetectors since its unique charges transfer characteristics and facile fabrication processes. Herein, a Si/ZnO nanowires/Ge quantum dots photodetector has been constructed via processes that combined electrospinni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…To improve the responsivity and photosensitivity of PDs based on ZnO NWs, modifications of ZnO NWs with various QDs have been proposed. 59,60 QDs can absorb more light and act as electron receptors to capture electrons under UV illumination, delay the recombination rate of carriers, and improve the conductivity and sensing performance of PDs. Shen et al fabricated a flexible PD using ZnO NWs modified by g-C 3 N 4 QDs.…”
Section: One-dimensional (1d) Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the responsivity and photosensitivity of PDs based on ZnO NWs, modifications of ZnO NWs with various QDs have been proposed. 59,60 QDs can absorb more light and act as electron receptors to capture electrons under UV illumination, delay the recombination rate of carriers, and improve the conductivity and sensing performance of PDs. Shen et al fabricated a flexible PD using ZnO NWs modified by g-C 3 N 4 QDs.…”
Section: One-dimensional (1d) Nanomaterialsmentioning
confidence: 99%
“…To improve the responsivity and photosensitivity of PDs based on ZnO NWs, modifications of ZnO NWs with various QDs have been proposed. 59,60…”
Section: Active Materials For Flexible Pdsmentioning
confidence: 99%
“…Hybrid structures based on CNT-ZnO composites have been researched primarily in the UV region [12][13][14] by exploiting the intrinsic attributes of CNTs that are already mentioned above and combining it with an already wellestablished [15] semiconductor material such as ZnO. ZnO based broad spectrum detectors have recently been reported by authors such as Jie et al [16] in their electro spun ZnO nanowires (NWs)/Ge quantum dots (QDs) structure with responsivity value of 172 mA W −1 over the UV-NIR range. Klochko et al [1] reported high spectral responsivity of 275 A W −1 and quantum efficiency as high as 9 × 10 4 % in their localized surface plasmon resonance mediated Ag modified ZnO film broad spectrum detector.…”
Section: Introductionmentioning
confidence: 99%
“…The spin coating method plays a significant role in the fabrication of Micro-Electro-Mechanical System (MEMS) devices [1], photodetectors [2], and diffraction optical elements [3]. Compared with the sol-gel method [4], vacuum deposition [5], dip-coating [6] and other thin film preparation methods, spin coating is more suitable for the preparation of uniform photoresist thin films due to its simple process, controllability and repeatability.…”
Section: Introductionmentioning
confidence: 99%